Chapter two-neuromechanics: From neurons to brain - Goriely, Alain; Budday, Silvia; Kuhl, Ellen (Advances in Applied Mechanics, 2015)
Arguably, the brain is the most complex organ in the human body, and, at the same time, the least well understood. Today, more than ever before, the human brain has become a subject of narcissistic study and fascination. The fields of neuroscience, neu- rology, neurosurgery, and neuroradiology have seen tremendous progress over the past two decades; yet, the field of neuromechanics remains underappreciated and poorly understood. Here, we show that mechanical stretch, strain, stress, and force play a critical role in modulating the structure and function of the brain. We discuss the role of neuromechanics across the scales, from individual neurons via neuronal tissue to the whole brain. We review current research highlights and discuss challenges and potential future directions. Using the nonlinear field theories of mechanics, we illustrate three phenomena which are tightly regulated by mechanical factors: neuroelasticity, the extremely soft behavior of the brain independent of time; neurodevelopment, the evo- lution of the brain at extremely long time scales; and neurodamage, the degradation of the brain at extremely short time scales. We hope that this review will become a starting point for a multidisciplinary approach to the mechanics of the brain with potential impact in preventing, diagnosing, and treating neurological disorders.